Preparing and Using Classroom Observations in Faculty Teaching Evaluations - Peggy A Thelen (Academic Chairpersons Conference Proceedings, 2015)
Department chairs charged with evaluating faculty teaching often receive no formal observation and assessment training. This session offers suggestions for the organization, implementation, and reflection of the faculty teaching evaluation process. We will also discuss the difficulties and successes of the faculty teaching evaluation process.
Keywords: assessment; evaluation; faculty; teaching; observation